PERSEPSI MASYARAKAT ATAS KINERJA DANA DESA PROVINSI JAWA TENGAH - Nurhidayati Nurhidayati (Universitas Nusa Cendana, 2023)
Empirically, the allocation of Village Funds has the potential to increase the output of infrastructure, health, and education, but is considered unable to improve welfare yet. Therefore, it is necessary to measure the assessment of the village community itself on the utilization of the Village Fund in their respective villages. This study aims to obtain the perception of rural communities in the Central Java Province regarding the performance of the Village Fund over the last few years. This research was conducted using a survey method to measure people's perceptions and then presented descriptively. Aspects that were measured in this survey are the development of physical development, assistance to the community, the adequacy of basic community needs, village apparatus services, as well as accountability, and community participation. As many as 487 respondents from 28 districts in Central Java filled out this survey. The results of the study indicated that during the last period, the village has experienced significant physical development, however, aspects of assistance to the community and services to the community still need to be improved. Keywords: Perception; Performance; Village Fund